Intervensi terapi pemaafan berbasis nilai-nilai Islam terhadap kebermaknaan hidup santri korban kekerasan: Studi eksperimen di Pondok Pesantren Al-Adabiy Pontianak - Sherli Kurnia Oktaviana; Ihsan Nurmansyah (Universitas Muhammadiyah Malang, 2026)
The high incidence of violence in Islamic boarding schools has a negative impact on students’ psychological well-being and meaning in life. This condition highlights the importance of interventions that not only address psychological aspects but also integrate spiritual dimensions. This study hypothesizes that Islamic-based forgiveness therapy can improve the meaning in life among students who are victims of violence in Islamic boarding schools. This study employed an experimental method with a pretest-posttest control group design. The participants were 24 students who were victims of violence, selected through purposive sampling and divided into two groups: an experimental group (12 students) and a control group (12 students). The instruments used included the Meaning in Life Scale based on Bastaman’s theory and the Forgiveness Scale developed by Nashori. Data were analyzed using paired sample t-tests and independent sample t-tests. The results indicated that Islamic-based forgiveness intervention was effective in significantly improving both meaning in life and forgiveness among student victims of violence in Islamic boarding schools. The mean score of meaning in life increased significantly from 50.25 at pretest to 74.25 at posttest (t = -34.467; p = 0.000). The experimental group demonstrated a consistent improvement through the follow-up phase, while the control group showed no significant change. The intervention, grounded in Islamic spiritual values, was shown to reduce negative emotions and strengthen positive psychological conditions in a sustainable manner, thereby contributing substantially to the development of Islamic-based psychological therapy in Islamic boarding school settings.